Fear-Free Cross-Cultural Communication: Toward a More Balanced Approach With Insight From Neuroscience - Nguyen-Phuong-Mai, Mai (Frontiers in Communication, 2020)
In cross-cultural communication and adjunct disciplines such as cross-cultural management and international business, there is a negativity bias of seeing cultural differences as a source of potential issues. The emergence of Positive Organizational Scholarship (POS) questions this problem-focused approach. This paper contributes to the ongoing discussion from neuroscience’s perspectives in several ways. Firstly, it provides a neurological look at this bias. Secondly, it proposes that that the problem-focused approach may (1) give us a biased outlook of cross-cultural encounters rather than a reality, (2) hinder creativity, (3) lead to the rebound effect, and (4) turn belief into reality. Finally, based on insight from neuroscience and adopting the POS lens with the connection between POS and creativity, it’s recommended that future research takes three directions: (1) Using similarity as the starting point; (2) strategize body language, context and theories; and (3) develop a multicultural mind. In essence, the paper contributes to existing knowledge of the field by employing an interdisciplinary approach, aiming to gain a more holistic view, provoke thoughts, and trigger future empirical studies.